ИЛК СИНОНИМ ЎҚУВ ЛУҒАТЛАРИНИНГ ПАЙДО БЎЛИШИ ВА ТАРАҚҚИЁТИ БОСҚИЧЛАРИ - Мирханова, Г.Р. (SCIENCE and SOCIETY, 2021)
This article describes synonymous words, which are an important means of expressive, complete and attractive expression of words and ideas, their study and understanding of synonymous dictionaries created in the history of world linguistics.